DESAIN MESIN LAMINAR AIR FLOW (LAF) DENGAN MENGGUNAKAN HMI PADA PT. ENTRI JAYA MAKMUR SURAKARTA - Farit Ardiyanto; Slamet Pambudi; Joko Yunianto Prihatin (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Laminar Air Flow (LAF) is a crucial device in microbiology laboratories, pharmaceutical facilities, and healthcare facilities, helping maintain sterile, contamination-free work areas. However, the LAF product was previously manufactured by PT. Entri Jaya Makmur was based on mechanical switches and a simple character LCD display, resulting in inefficiency, minimal operational monitoring features, and low market appeal. This community service project aims to improve the product's functionality and sales value by modernizing the control system with a Nextion-based touchscreen Human-Machine Interface (HMI). This HMI not only replaces analog buttons but also adds various features such as timer settings, operating hours, HEPA filter life alarms, and UV light safety indicators, enhancing user safety and ease of operation. The attractive graphic design and more intuitive interface have been shown to improve perceived quality and consumer preference. The implementation results showed a significant increase in sales, from just one unit per month to three units in the first month of the new design's launch. Thus, HMI-based LAF modernization has proven effective in increasing the competitiveness of local products, supporting domestic market penetration, and contributing to the provision of healthcare facilities that meet national standards and align with the domestic medical device independence program.